Organizational commitment and burnout syndrome in Peruvian university teachers - Céspedes Vargas Machuca, Sandra (2022)
The objective of the research was to examine the relationship between organizational commitment and burnout syndrome in university teachers. The research was basic, non-experimental, cross-sectional and descriptive-correlational. We worked with 129 full-time teachers. They were administered the Organizational Commitment Questionnaire and the evaluation of burnout syndrome, duly validated and with good reliability. An inverse and significant correlation (Rho= -0.462 p<0.05) was found between organizational commitment and burnout syndrome in the evaluated teachers.